Mobility at the margins - Cairns, D.; Malet Calvo, D.; Clemente, M. (The Palgrave handbook of youth mobility and educational migration, 2021)
The final part of this book looks at several undercurrents within youth mobility research, many of which have not featured prominently in mainstream studies in this field. In terming this section ‘mobility at the margins,’ there is also acknowledgement that while moving for education, work or training has been a relatively normative expectation for many young people for many years, there are still forms of youth circulation that are relatively undocumented or misunderstood, perhaps due to a certain level of discomfort in coming to terms with certain situations. Academic research has tended to emphasise the wide variety of individual lifestyle benefits and further professional possibilities available to young people who move, leaving the task of documenting the negative aspects to journalists, with policymakers perhaps preferring to finance interventions via civil society organizations (with limited budgets for conducting research) or focusing on issues that reflect politicians’ own beliefs rather than the voices of migrants. As such, we lack critical engagement with the consequences of exploitation within youth mobility, with a failure to recognize the unsustainability of the hegemonic neoliberal view of young people’s circulation as a means of generating economic capital for external parties such as universities. This extends to repercussions emerging from the rapid expansion of both the modes of travel and heightened levels of circulation, in addition to what are often quite obvious vulnerabilities within fragmented migration trajectories (see also Cairns 2021a, 2021b).